Mortality and morbidity of pregnant woman with COVID- 19 Infection : A meta analysis - Aida Musyarrofah; Anung Putri Illahika; Probo Yudha Pratama Putra; Dinda Amalia Eka Putri; S.Khansa Zatalini; Yohanes Eddy Prasetyo (International Journal of Public Health Science (IJPHS), 2022)
Coronavirus disease 2019 (COVID-19) is caused by SARS-CoV-2 and declared as a global pandemic in March 2020. There is a special immune tolerance in pregnant woman, predisposes to a viral infection, then increased risk severe complication. A comprehensive literature study was performed in July 2021 through Science Direct, Cochrane, and PubMed, with keywords “COVID-19”, “SARS-CoV-2”, “Pregnancy”, “Pregnant”, and “Complication”. Nine studies with 30.257 infected patients and 1.678.974 non infected patients were included. The data show that preterm birth (OR=1.43, 95% CI: 1.17-1.74; p = 0.0004, I2=90%) less in non infected groups, no camparable finding in vaginal delivery (OR =0.93, 95% CI: 0.82-1.06; p<0.030, I2=75%) and caesarian delivery (OR =1.07, 95% CI: 0.90-1.28; p<0.045, I2=96%). ICU admission reported high percentage in infected patients (OR =4.87, 95% CI: 3.08-7.71; p<0.0001, I2=93%), we found that obstetric complication in subgroup (OR =1.31, 95% CI: 0.13-1.52; p<0.0003,I2=54%) and mortality (OR =17.41, 95% CI: 11.04-27.46; p<0.0001, I2=0%) less in non infected patients. Pregnancy with infected COVID-19 has high percentage of mortality and morbidity events. Infected and non infected patients has equal chance for vaginal or caesarian delivery.